Direct Oral Anticoagulants as Successful Treatment of Heparin-Induced Thrombocytopenia: A Parisian Retrospective Case Series - Julie Carré (Frontiers in Medicine, 2021)
Background: Heparin-induced thrombocytopenia (HIT) is a prothrombotic life-threatening disorder caused by an adverse reaction to heparin exposure. In this context, it is imperative to stop heparin immediately and to replace it by a non-heparin anticoagulant therapy. Despite their advantages, the use of direct oral anticoagulants (DOACs) is only emerging for HIT treatment, and their use remains rare.Objective: To improve our knowledge on the emerging role of DOACs as treatment of HIT and give an overview of our local practices in this context.Patients/Methods: This is a multi-centric retrospective case series of HIT patients referred to our Parisian pharmacovigilance network and treated with DOACs.Results: We report the cases of seven patients from four healthcare centers, diagnosed with HIT (4T score ≥ 4, positive anti-PF4/heparin immunoassay and positive serotonin-release assay) and treated with DOACs. After a few days on substitutive parenteral treatment (n = 6) or directly at HIT diagnosis (n = 1), these patients were treated with either rivaroxaban (n = 6) or apixaban (n = 1) during acute HIT phase. Mean time to platelet count recovery after heparin discontinuation was 3.3 days (range 3–5). No patient experienced major or clinically relevant non-major bleeding or thrombosis that could be related to DOAC treatment during follow-up.Conclusions: Our cases studies are consistent with recent guidelines credit to the potential and safe use of DOAC during acute HIT in clinically stable patients.